2011
DOI: 10.1111/j.1463-1318.2009.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of macroscopic completeness of mesorectal resection in rectal cancer

Abstract: The outcome of surgical treatment of rectal cancer is related to the completeness of mesorectal excision. It is a more discriminative prognostic factor than the classic tumour-node-metastasis (TNM) system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 16 publications
4
34
1
2
Order By: Relevance
“…The results of Maslekar et al confirmed that grade of mesorectun independently influenced both local and overall recurrences [21]. Meanwhile, Leite et al revealed that the mesorectal score was an independent factor for local recurrence and disease-free survival [22]. Furthermore, Lino-Silva et al used a two-grade system to determine the prognostic value of the mesorectum quality, and results suggested that inadequate mesorectum was correlated with R1/R2 resections, positive margins, and decrease survival, so the two-grade system (adequate, inadequate) was proposed [23].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Maslekar et al confirmed that grade of mesorectun independently influenced both local and overall recurrences [21]. Meanwhile, Leite et al revealed that the mesorectal score was an independent factor for local recurrence and disease-free survival [22]. Furthermore, Lino-Silva et al used a two-grade system to determine the prognostic value of the mesorectum quality, and results suggested that inadequate mesorectum was correlated with R1/R2 resections, positive margins, and decrease survival, so the two-grade system (adequate, inadequate) was proposed [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our study on low rectal cancer we reported the surgical quality of APR specimens only, and this may explain the high percentage of muscularis propria resection planes [14]. The results reported by Leite et al (2009) [18] may be explained as a reflection of the individual performance of a single center, whereas Leonard et al (2010) [20•] describe an audit of the performance of 33 potential expert surgeons from multiple centers in Belgium. Surgeons in the latter study are candidate-TME-trainers, who agreed to an external audit of their consecutive TME cases to judge whether they could serve as an alternative to foreign TME experts in a national teaching program.…”
Section: Incidencementioning
confidence: 96%
“…Bei intaktem Mesorektum betrug das 5-Jahres-tumorfreieÜberleben 65 % im Vergleich zu 47 % bei Defekten des Mesorektums (P< 0,05) [831]. Nach 3 Jahren Follow-up betrug die Lokalrezidivrate bei intakter mesorektaler Faszie 4 % (3 -6 %), 7 % (5 -11 %) bei intramesorektalen Einrissen, und 13 % (8 -21 %) bei Erreichen der Muscularis-propria-Ebene [827].…”
Section: Multiviszerale Resektionunclassified